Molecular Cloning and Characterization of Juvenile Hormone Acid Methyltransferase in the Honey Bee, Apis mellifera, and Its Differential Expression during Caste Differentiation - Li, Wenfeng; Huang, Zachary Y.; Liu, Fang; Li, Zhiguo; Yan, Limin; Zhang, Shaowu; Chen, Shenglu; Zhong, Boxiong; Su, Songkun (PLOS ONE, 2013)
Juvenile hormone acid methyltransferase (JHAMT) is an enzyme involved in one of the final steps of juvenile hormone biosynthesis in insects. It transfers a methyl group from S-adenosyl-L-methionine (SAM) to the carboxyl group of either farnesoic acid (FA) or JH acid (JHA). Several genes coding for JHAMT have been cloned and characterized from insects from different orders, and they have been shown to play critical roles in metamorphosis and reproduction. However, the significance of JHAMT in Hymenopteran insects is unknown. We used RACE amplification method to clone JHAMT cDNA from the honey bee, Apis mellifera (AmJHAMT). The full length cDNA of AmJHAMT that we cloned is 1253bp long and encodes a 278-aa protein that shares 32-36% identity with known JHAMTs. A SAM-binding motif, conserved in the SAM-dependent methyltransferase (SAM-MT) superfamily, is present in AmJHAMT. Its secondary structure also contains a typical SAM-MT fold. Most of the active sites bound with SAM and substrates (JHA or FA) are conserved in AmJHAMT as in other JHAMT orthologs. Phylogenetic analysis clustered AmJHAMT with the other orthologs from Hymenoptera to form a major clade in the phylogenetic tree. Purified recombinant AmJHAMT protein expressed in E. coli was used to produce polyclonal antibodies and to verify the identity of AmJHAMT by immunoblotting and mass spectrometry. Quantitative RT-PCR and immunoblotting analyses revealed that queen larvae contained significantly higher levels of AmJHAMT mRNA and protein than worker larvae during the periods of caste development. The temporal profiles of both AmJHAMT mRNA and protein in queens and workers showed a similar pattern as the JH biosynthesis. These results suggest that the gene that we cloned codes for a functional JHAMT that catalyzes the final reactions of JH biosynthesis in honey bees. In addition, AmJHAMT may play an important role in honey bee caste differentiation.